Weathering products in glacial silt and clay: Using automated mineralogy to probe size distribution and source - Jeffrey W. Crompton (Arctic, Antarctic, and Alpine Research)
Clay minerals are ubiquitous in glacial sediment, but their source is debated. In this study, automated mineralogy is used to characterize the size distribution of weathering products from bedrock and glacial sediment collected from multiple glacier basins in the St. Elias Mountains, Yukon, Canada. In comparing sediment to bedrock, biotite and chlorite show a relative decrease in Mg-rich phases and an alteration to smectite and vermiculite, respectively, with a dependence on grain size. Plagioclase undergoes a relative decrease in calcic versus sodic components, also with a dependence on grain size. Other minor differences between rock and sediment include a change from dolomite to a more Fe-rich dolomite, an increase in the dolomite content on the edge of calcite grains, an increase in kaolinite with sodic plagioclase, an increase in laumontite with calcic plagioclase, and an increase in talc with pyroxene. Minerals likely undergo preweathering in the near-surface bedrock prior to weathering in sediment in channelized and distributed subglacial waters. Characterizing the mineral alterations that occur subglacially is a step toward identifying the chemical weathering reactions that control the balance of dissolved species in glacial meltwaters and a step toward understanding the source of clay minerals from present and past glacial environments.